تأثير منهج إرشادي نفسي في تعديل السلوك الاجتماعي وتطوير دقة أداء بعض أشكال الضرب الساحق للاعبي الكرة الطائرة - الدليمي، ناهدة عبد زيد بعيوي; السناني، يسرى بنت جمعة; البزيني، شهلة أحمد عبدالله شيخ (جامعة حلوان - كلية التربية الرياضية للبنين, 2022)
يعد السلوك الاجتماعي من أهم الظواهر الاجتماعية في المجتمع لأنه وسيلة الاتصال بين الأفراد، ويتم هذا الاتصال من خلال التفاعل والتعاون والمشاركة فيما بينهم ونقل الفكر بأبعاده المختلفة من فرد إلى أخر ومن جماعة إلى أخرى، فالفرد يكتسب سلوكه الاجتماعي من المجتمع الذي يعيش فيه ومنذ طفولته فيتأثر هذا السلوك بالبيئة التي يعيش فيها وبأوجه الأنشطة التي يمارسها عبر علاقاته بمن يحيط به، ولكي يكون الفرد متوافقا اجتماعيا، ومن خلال متابعة الباحثات لاحظن أن نسبة كبيرة من لاعبي منتخبات الجامعات العراقية بالكرة الطائرة يواجهون مشكلات في تكيفهم السلوكي الاجتماعي، من حيث ضعف مهاراتهم الشخصية لإقامة علاقات جيدة مع اللاعبين الآخرين ومهارات التعاون، والمشاركة في النشاطات والفعاليات الاجتماعية، فضلا عن ملاحظة الباحثات لقلة المناهج الإرشادية النفسية المتخصصة بتطوير السلوك الاجتماعي المرغوب فيه والحد من السلوك الاجتماعي غير المرغوب فيه الذي أخذ يظهر على نحو واضح في الفترة الأخيرة، ومن هنا شعرت الباحثات بوجود مشكلة حقيقية لها أثارها السلبية سواء على اللاعبين أم على منتخباتهم والمجتمع المحيط بهم، والمتمثلة في ضعف السلوك الاجتماعي لديهم، وتحددت أهداف البحث بإعداد مقياس السلوك الاجتماعي، فضلا عن التعرف على تأثير هذا المنهج في تعديل السلوك الاجتماعي وتطوير دقة أداء بعض أشكال الضرب الساحق للاعبي الكرة الطائرة، وتم أتباع المنهج التجريبي بتصميم المجموعة الفردية ذات الاختبارين القبلي والبعدي، وتوصلت الباحثات إلى استنتاجات عدة من أهمها: للمنهج الإرشادي النفسي الذي أعتمد ضمن الوحدات التدريبية دور كبير وإيجابي في تعديل السلوك الاجتماعي للاعبي الكرة الطائرة، فضلا عن مساهمة هذا المنهج في تطوير دقة أداء بعض أشكال الضرب الساحق بالكرة الطائرة، وفي ضوء هذه الاستنتاجات أوصت الباحثات بضرورة اعتماد المنهج الإرشادي النفسي ضمن الوحدات التدريبية للاعبي الكرة الطائرة لتطوير السلوك الاجتماعي لديهم، مع ضرورة اهتمام مدربي الكرة الطائرة بالإرشاد النفسي للاعبين، وتخصيص جلسات إرشادية كافية في الوحدات التدريبية. Social behavior is one of the most important social phenomena in society because it is a means of communication between individuals, and this communication takes place through interaction, cooperation and participation among them and the transfer of thought in its various dimensions from one individual to another and from one group to another. This behavior in the environment in which he lives and in the aspects of the activities he practices through his relationships with those around him, and in order for the individual to be socially compatible, and through the follow-up of the researchers, they noticed that a large percentage of Iraqi university volleyball players face problems in their social behavioral adjustment, in terms of weak personal skills to establish Good relations with other players, cooperation skills, and participation in social activities and events, as well as the researchers’ observation of the lack of specialized psychological counseling methods for developing desirable social behavior and limiting unwanted social behavior that has appeared clearly in the recent period. Hence, the researchers felt the existence of A real problem that has negative effects, whether on the players or on their teams and the community around them, represented in weakness Their social behavior, and the objectives of the research were determined by preparing a social behavior scale, as well as recognizing the effect of this approach in modifying social behavior and developing the accuracy of the performance of some forms of smash hits for volleyball players. Several of the most important of them: The psychological counseling approach that was adopted within the training units has a significant and positive role in modifying the social behavior of volleyball players, as well as the contribution of this approach to developing the accuracy of the performance of some forms of volleyball crushing, and in light of these conclusions, the researchers recommended the necessity of adopting the psychological counseling approach Within the training units for volleyball players to develop their social behavior, with the need for volleyball coaches to pay attention to psychological counseling for players, and to allocate sufficient counseling sessions in the training units.
Keywords: التفاعل الاجتماعي -- السلوك الاجتماعي -- المهارات النفسية -- الإرشاد النفسي